The Relationship of Population's Knowledge, Attitudes, and Communication with Population's Participation in the Mangrove Rehabilitation Program in Pulau Cawan Village, Mandah District, Indragiri Hilir District, Riau Province - Ramadhan, Rizki; Zulkarnain, Zulkarnain; Nugroho, Firman (Fakultas Perikanan dan Kelautan Universitas Riau, 2024)
This research was conducted in December 2023 in Pulau Cawan Village, Mandah District, Indragiri Hilir Regency, Riau Province. This research aims to analyze residents' knowledge, attitudes, and communication toward mangrove rehabilitation programs; analyze residents' participation in the mangrove rehabilitation program; analyze the relationship between residents' knowledge, attitudes, and communication with residents' participation in the mangrove rehabilitation program in Pulau Cawan Village. The research method used was a quantitative survey. Respondents of this study amounted to 30 households. To answer the research objectives, researchers used Likert Scale data analysis to answer the second objective, while for the third objective, researchers used Spearman Rank data analysis. The study results were population knowledge at a score of 1.178, population attitudes at a score of 1.178, and population communication at a score of 1.176, meaning that population knowledge, attitudes, and communication were outstanding. Good in the Mangrove rehabilitation program. Meanwhile, resident participation obtained a score of 1.492, which means that resident participation is quite good in the Mangrove rehabilitation program. The relationship between population knowledge and population participation is 00.529, population attitudes and population participation is 0.401, and the relationship between population communication and population participation is 0.422, so it can be interpreted as a moderate level of relationship closeness. If the sig value (2-tailed) <0.05, it can be considered significant.